P.011 Piano Player Hand Sign: description of a novel clinical sign elicited by cortical electrical stimulation in epileptic patients. (June 2022) - Brochu, K; Martineau, L; Martin, G; Hoffmann, D; Chabardes, S; Minotti, L; Kahane, P
Abstract : Background: Cortical electrical stimulation (CES) may produce different motor responses according to the brain area stimulated. In this study, we describe a new motor response characterized by finger movements such as a person playing piano, which we named the Piano Player Hand (PPH) sign. Methods: We retrospectively reviewed the CES results of 252 patients with drug-resistant epilepsy who underwent SEEG between January 2005 and December 2019 at the Grenoble-Alpes University Hospital. The patients' characteristics, SEEG findings and CES parameters were extracted to find common clinical and anatomical features. Results: The PPH sign was identified 20 times from 12 patients, with stimulation of either the supplementary motor area (SMA), anterior cingulate gyrus (ACG), pre-SMA, middle frontal gyrus and anterior insula. It was obtained with high frequency stimulation, with intensity ranging from 0, 7 to 3mA and mostly contralateral to the stimulation side (19/20). It was part of the ictal semiology of five patients. An afterdischarge was observed in five of the relevant CES. Conclusions: The PPH sign is a novel clinical sign, obtained mainly, but not exclusively, with CES of a small vicinity encompassing the SMA, pre-SMA and ACG. The PPH sign, when occurring ictally, may point to the premotor mesial frontal surface of the brain.